Ga2O3/Ag/Ga2O3-Laminated Film Fabricated at Room Temperature: Toward Applications in Ultraviolet Transparent Highly Conductive Electrodes - Kexiong Zhang; Lei Feng; Lei Wang; Jun Zhu; Hai Zhang; Sihua Ha; Jiajun Sun; Hongwei Liang; Tianpeng Yang (Crystals, 2023)
Ga2O3/Ag/Ga2O3-laminated films with high electrical conductivity and ultraviolet (UV) transparency were achieved by radio frequency magnetron sputtering at room temperature (RT) on quartz glass. The influence of annealing temperature and ambient on the structural, electrical and optical properties of Ga2O3/Ag/Ga2O3-laminated films were investigated in detail. As the annealing temperature increases, the optical bandgap of the Ga2O3-laminated films widens. The Ga2O3/Ag/Ga2O3-laminated films exhibited good photoelectric performance with a figure-of-merit (FOM) value of 5.83 × 10−3 Ω−1, a sheet resistance of 12.55 Ω/sq, a transmittance of 95.15% at 325 nm, and an average transmittance of 77.56% (250~300 nm). All these results suggest that RT-fabricated Ga2O3/Ag/Ga2O3-laminated films show great potential in UV transparent conductive electrodes for UV optoelectronic devices and in flexible electronics.